2019
DOI: 10.1590/0100-29452019642
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock-scion interaction:3. Effect on the composition of Cabernet Sauvignon wine

Abstract: The interaction among rootstock, scion and environment may induce different responses to the grapevine physiology and consequently to the grape and wine composition. The vineyards of Serra Gaúcha, Brazil, are established in soils that may have different physicochemical attributes. Furthermore, the grapevines are grafted on a wide diversity of rootstocks. Therefore, this study aimed to determine their effect on the wine composition of the Cabernet Sauvignon (CS) grafted on Rupestris du Lot, 101-14 Mgt, 3309 C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…However, Merlot wine group was higher (p< 0.05) in total polyphenols index (19.5%), A 520 (46.7%), and color intensity (32.1%). In general, the data of the present study are similar to those already recorded in previous studies conducted in the same region on Merlot (Miele et al, 2009b) and Cabernet Sauvignon (Miele & Rizzon, 2019) wines. Polyphenols are very complex, important compounds for red wines, with anthocyanins and tannins the main substances in this group that could influence the characteristics and quality of the wine.…”
Section: Classical Variablessupporting
confidence: 92%
See 1 more Smart Citation
“…However, Merlot wine group was higher (p< 0.05) in total polyphenols index (19.5%), A 520 (46.7%), and color intensity (32.1%). In general, the data of the present study are similar to those already recorded in previous studies conducted in the same region on Merlot (Miele et al, 2009b) and Cabernet Sauvignon (Miele & Rizzon, 2019) wines. Polyphenols are very complex, important compounds for red wines, with anthocyanins and tannins the main substances in this group that could influence the characteristics and quality of the wine.…”
Section: Classical Variablessupporting
confidence: 92%
“…The methanol contents (Table 3) of all wines were lower (mean of 215.4 mg/L) than 300 mg/L specified by Brazilian law. Nevertheless, methanol was about 50% higher than found in other studies carried out in the same region (Miele & Rizzon, 2019). This alcohol is synthesized by the hydrolysis of pectin present in grape berries, mostly in the skin.…”
Section: Volatile Compoundsmentioning
confidence: 56%
“…The importance of maintaining wines with lower contents of volatile acidity relies on the fact that this parameter may negatively influence wine nutritional quality and sensory characteristics. Miele and Rizzon (2019) observed no statistical differences in volatile acidity (ranging from 12-14 meq L −1 ) for Cabernet Sauvignon wines grafted under different rootstocks. In the present study, rootstocks IAC-572 (harvest I and II) and Paulsen 1103 (harvest II) rendered a decreased volatile acidity.…”
Section: Physicochemical Characteristicsmentioning
confidence: 69%
“…Regardless of the training system, the IAC 766 rootstock resulted in wines with the highest alcoholic content for the harvest I, with no significant differences concerning the rootstock in harvest II for the majority of samples. Miele and Rizzon (2019) suggested that alcohol content is one of the variables most affected by the rootstocks system in Cabernet Sauvignon wines.…”
Section: Physicochemical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation